Recycling of HDPE-giant reed composites: Processability and performance - Suárez Luis; Barczewski Mateusz; Billham Mark; Miklaszewski Andrzej; Mietliński Patryk; Ortega Zaida (Green Processing and Synthesis)
Giant reed (Arundo donax), a plant species with potential for obtaining lignocellulosic fibres, was validated as reinforcement in thermoplastic composites with good processability, thermo-mechanical performance, and aesthetics. This study evaluates the impact of closed-loop recycling of high-density polyethylene (HDPE)-based composites with up to 40% of reed fillers: fibres and shredded plants, on their processing and application properties. Arundo fillers do not significantly impact the processing stability and performance of recycled composites and can improve some aspects. Minor chemical composition differences were observed, highlighting oxidation resistance. All formulations keep their viscous character and reduce the melt flow index slightly, benefiting reprocessing due to the absence of degradation-prone coupling agents. The composites remain thermally stable up to 230°C, with only slight weight loss at 160°C due to lignocellulosic filler degradation. Fillers lead to longer oxidation induction time compared to neat HDPE. Reprocessed moulded materials show higher stiffness and improved ultimate tensile and flexural strength, but lower impact resistance due to shorter filler length. Smaller fillers and improved matrix distribution also reduce water uptake. Fibrous fillers reduce the aspect ratio, making composites with shredded reed more similar to reed fibres, which are costlier to produce. Shortening of the reprocessed fibrous filler is associated with increased crystallinity in composite materials.